Reconstruction and optimization of a Pseudomonas putida-Escherichia coli microbial consortium for mcl-PHA production from lignocellulosic biomass - Qin, Ruolin; Zhu, Yinzhuang; Ai, Mingmei; Jia, Xiaoqiang (Frontiers in Bioengineering and Biotechnology, 2022)
The demand for non-petroleum-based, especially biodegradable plastics has been on the rise in the last decades and mcl-PHA produced from renewable feedstocks has become the focus of research. In recent years, researchers aimed to overcome the disadvantages of single strains, and artificial microbial consortia have been developed into efficient platforms. In this work, we reconstructed the previously developed microbial consortium composed of engineered Pseudomonas putida and Escherichia coli. The maximum yield of mcl-PHA reached 3.98 g/L using 10 g/L glucose, 5 g/L octanoic acid as substrates by P. putida. On the other hand, the maximum synthesis capacity of the engineered E. coli was further enhanced to produce 3.38 g/L acetic acid and 0.67 g/L free fatty acids (FFAs) using 10 g/L xylose. Based on the concept of “nutrient supply-detoxification”, the E. coli provided nutrient for the engineered P. putida and the P. putida acted to detoxify the substrates. Through the above functional division and rational design of metabolic pathways, the P. putida-E. coli microbial consortium could produce 1.30 g/L of mcl-PHA from 10 g/L glucose and xylose. Furthermore, the consortium finally produced 1.02 g/L of mcl-PHA using lignocellulosic hydrolysate with 10.50 g/L glucose and 10.21 g/L xylose. The consortium developed in this study has good potential for mcl-PHA production and provides a valuable reference for the production of high-value biological products using inexpensive carbon sources.